Analysis of the Effect of Perceptions on The Distribution of Medical Services for BPJS Patients and Organizational Climate on Job Satisfaction of Doctors at Royal Prima Medan Hospital - Rini Elvira Hutabarat; Adek Amansyah; Ali Napiah Nasution; Tan Suyono (International Journal of Health and Pharmaceutical (IJHP), 2022)
Job satisfaction among doctors is the main key to getting better health services. Changes in payment methods in the JKN era led to the dissatisfaction of specialists and general practitioners with the medical services received in BPJS patient care. This study analyzes the effect of perceptions about the distribution of medical services for BPJS patients on the job satisfaction of doctors. The research design used in this study was a descriptive analytic non-experimental study with a cross-sectional approach. The study was conducted at the Royal Prima General Hospital located in Medan City from May 2021 to August 2021. The sample in this study was selected using the purposive sampling method so that a sample of 77 people was obtained with the inclusion criteria of having worked for at least 2 years. Data were analyzed using the Chi-Square test and multiple logistic regression. The results showed that the total medical services received by general practitioners per month was 10 million rupiah. Meanwhile, the total number of medical visits and services received by specialist doctors per month is 25 million rupiah. Based on the results of the Chi-Square test, it can be seen that doctors' perceptions of medical services (number of medical services (p = 0.000), timeliness of delivery (p = 0.000), suitability of medical services with performance (p = 0.003), distribution system (p = 0.004), and transparency (p=0.011)) had a significant effect on doctor's job satisfaction. The results of multiple logistic regression test show that the variable with the greatest influence is the number of medical services. The variable number of medical services has a value of Exp(B) = 29,830 (95% CI 3,037-293,034) that means that respondents who state the number of good medical services are 29 times more likely to be satisfied than those who state that the number of medical services is less. Doctor's job satisfaction can be increased by the management's efforts to be more open to doctors regarding doctor's medical services, giving doctors the opportunity to improve their career paths, and conducting periodic evaluations of doctor's satisfaction through questionnaires.